Comparison of 24 hour urine and 24 hour diet recall for estimating dietary sodium intake in populations: systematic review and meta-analysis - McLean, R; Cameron, C; Butcher, E; Cook, N; Woodward, M; Campbell, N (Wiley, 2019)
This systematic literature review and meta‐analysis examined whether 24‐hour diet recall is a valid way to measure mean population sodium intake compared with the gold standard 24‐hour urinary assessment. The authors searched electronic databases MEDLINE, Embase, and Scopus using pre‐defined terms. Studies were eligible for inclusion if they assessed adult humans in free‐living settings, and if they included group means for 24‐hour diet recall and 24‐hour urinary collection of sodium intake in the same participants. Studies that included populations with an active disease state that might interfere with normal sodium metabolism were excluded. Results of 28 studies are included in the meta‐analysis. Overall, 24‐hour diet recall underestimated population mean sodium intake by an average of 607 mg per day compared to the 24‐hour urine collection. The difference between measures from 24‐hour urine and 24‐hour diet recall was smaller in studies conducted in high‐income countries, in studies where multiple‐pass methods of 24‐hour diet recall were reported and where urine was validated for completeness. Higher quality studies also reported smaller differences between measures than lower quality studies. Monitoring of population sodium intake with 24‐hour urinary excretion remains the most accurate method of assessment. Twenty‐four‐hour diet recall tends to underestimate intake, although high‐quality 24‐hour diet recall improves accuracy, and may be used if 24‐hour urine is not feasible.